Numerical Simulation of Gas-Particle Two-Phase Flow in a Nozzle with DG Method - Duan Maochang; Yu Xijun; Chen Dawei; Qing Fang; Zou Shijun (Discrete Dynamics in Nature and Society)
In this paper, the discontinuous Galerkin (DG) method is applied to solve the governing equations of the dispersed two-phase flow with the two-fluid Euler/Euler approach. The resulting governing equations are simple in form and the solution process is very natural. The characteristics of the gas-particle two-phase flow in an engine nozzle are mainly analyzed, and the impacts of the particle mass fraction and particle size on the flow field and engine performance are evaluated. Because of the addition of particles, the gas flow field undergoes significant modifications. Increase in the mass fraction leads to a significant thrust loss in the gas phase, and the impact of the particles on the gas phase could be substantial. Therefore, a quantitative study of thrust loss in the nozzle due to the particle impact is made. It is found that the gas thrust in the two-phase flow is reduced, but the total thrust of the two-phase flow increases to a certain extent.